EFEKTIVITAS PELAYANAN PERANGKAT DESA OLEH KEPEMIMPINAN KEPALA DESA (DATUK PENGHULU) - Hardiansyah, Muhammad; Nasution, Muhammad Arif; Matondang, Armansyah (PERSPEKTIF, 2019)
This study aims to determine the extent of the Leadership of the Village Head (Datuk Penghulu) on the Effectiveness of Village Service Services in the Community of Aceh Tamiang District Health Village in 2017. Leaders can influence morale, job satisfaction, security, work quality and especially the level of achievement of an organization.  The ability and skills in direction are important factors for the effectiveness of an organization. By looking at several aspects to determine the effect of Leadership and Measurement of Service Effectiveness in the Health Village of Karang Baru Subdistrict, Aceh Tamiang Regency, namely: loyalty, Decision Making Communication, Responsibility and Obedience of leaders to regulations. in this study using a qualitative descriptive method, the location of the study was conducted in the Health Village of Karang Baru sub-district, Aceh Tamiang Regency. Data collection techniques are interviews, observation and documentation, it can be concluded that the Leadership of the Village Head (Datuk Penghulu) Against the Effectiveness of Service of Village Devices in the Community of Aceh Tamiang District Health Village in 2017 has been good.